Antimicrobial activities, toxicity and phenolic composition of Asphodeline anatolica E. Tuzlaci leaf extracts from Turkey. Issue 22 (16th November 2016) - Marino, Andreana; Zengin, Gokhan; Nostro, Antonia; Ginestra, Giovanna; Dugo, Paola; Cacciola, Francesco; Miceli, Natalizia; Taviano, Maria Fernanda; Filocamo, Angela; Bisignano, Giuseppe; Aktumsek, Abdurrahman
Abstract: The antimicrobial activity of acetone, methanol and aqueous extracts of Asphodeline anatolica E. Tuzlaci leaves was evaluated against American type culture collection, food and clinical isolates ( Listeria monocytogenes and Staphylococcus aureus including methicillin-resistant strains-MRSA). Biofilm formation, toxicity and characterisation of the polyphenolic content were analysed. The acetone extract demonstrated a higher antibacterial activity against S. aureus including MRSA strains, L. monocytogenes and Pseudomonas aeruginosa than against other extracts. No effect was observed in biofilm formation. The extracts resulted non-toxic against Artemia salina Leach. The phytochemical screening of extracts indicated that they mainly contained six polyphenols identified as catechin 3-O-gallate, protocatechuic acid, diosmin, rutin, cirsimaritin and kaempferol glucoside. This study is the first report on antimicrobial activity and phenolic content of A. anatolica and contributes to enrich the literature data on the biological properties of this plant. A. anatolica leaves have a potential as source of natural antimicrobial compounds. Abstract :